THE IMPROVEMENT OF PURCHASE DECISIONS OF PUTRA KUSUMA PIA CAKE THROUGH PRODUCT QUALITY, PRODUCT VARIATIONS, AND PACKAGING - Hapsawati Taan, Rizan Machmud (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to discover and analyze (1) the impact of product quality towards purchase decisions, (2) the impact of product variation towards purchase decisions, (3) the impact of packaging towards purchase decisions, (4) the impact of product quality, product variation, and packaging towards purchase decisions. The population of the research is the number of customers from Putra Kusuma Gorontalo Pia Cake Shop. The sampling technique is Accidental Sampling, and the number of the samples is as much as 97 respondents. This research applies Multiple Linear Regression Analysis. The results discover that product quality, product variations, and packaging on purchase decisions had a positive and significant effects. It finds out that these three aspects are one of the important parts of a product to determine the level of purchase decisions. Quality, product variety, and packaging is a marketing strategy and an essential part of a product in making a purchase. Suggestions: To improve product quality and product variations, Putra Kusuma Pia Cake, it is recommended to increase the product variations. To improve the packaging, it is better to enhance the packaging by displaying images of a product with regard to the color and the shape as well as there must be any consistency between a product and an image of a product.